2011
DOI: 10.3168/jds.2010-3115
|View full text |Cite
|
Sign up to set email alerts
|

The whey fermentation product malleable protein matrix decreases triglyceride concentrations in subjects with hypercholesterolemia: A randomized placebo-controlled trial

Abstract: Malleable protein matrix (MPM) is a unique whey-derived ingredient obtained through a fermentation process using proprietary lactic acid bacteria strains from the Lactobacillus kefiranofaciens species. Because evidence from animal models suggests that MPM decreases serum lipid concentrations, the purpose of the present trial was to assess the hypothesis that MPM exerts lipid-lowering effects in humans. A total of 161 subjects (50% male; age 54.5 ± 9.8 yr, body mass index 26.3 ± 3.6 kg/m(2)) with hypercholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…The most common adverse effects were of gastro-intestinal nature, such as diarrhoea, flatulence, nausea and upper abdominal discomfort (see Table 7). These results are in agreement with our recent findings that in patients with hypercholesterolaemia, MPM decreases TAG concentrations by approximately 10 % (16) . Supplementation with MPM has previously been shown to have TAG-and LDL-C-lowering properties as well as FPG-and BP-modulating effects in animal models (15) .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The most common adverse effects were of gastro-intestinal nature, such as diarrhoea, flatulence, nausea and upper abdominal discomfort (see Table 7). These results are in agreement with our recent findings that in patients with hypercholesterolaemia, MPM decreases TAG concentrations by approximately 10 % (16) . Supplementation with MPM has previously been shown to have TAG-and LDL-C-lowering properties as well as FPG-and BP-modulating effects in animal models (15) .…”
Section: Discussionsupporting
confidence: 94%
“…Bortolotti et al ( 10 ) used a whey protein supplement in obese females (60 g/d over 4 weeks) and showed that fasting TAG decreased by 15 %. Our group has recently studied, in a randomised, double-blind, 12-week trial, the effects of MPM (2 × 15 g/d) on lipoprotein concentrations in 161 subjects with hypercholesterolaemia and observed a 10 % decrease in TAG in the MPM group compared to placebo ( 16 ) . Some studies involving subjects with moderate hypercholesterolaemia report lipid-lowering activities of fermented milk products containing live bacteria such as lactobacilli and bifidobacteria ( 39 – 43 ) , but it is unlikely that the observed effect of MPM on lipids come from such probiotic properties since the Lactobacillus strain used in the production of MPM is heat-killed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We speculated that the increase of TC in the OVXN mice and the increase of LDL-C in both the OVXN and the OVXH mice was also caused by the decrease of the physiological function in eliminating them. The situation of normal fasting glucose and normal TG concentration in serum of hypercholesterolemia patients have also been reported previously ( 54 57 ). It indicated that ovaries might have very important functions in eliminating TC and LDL-C in females.…”
Section: Discussionsupporting
confidence: 75%
“…Similar observations have been made in a clinical setting. Reduced intrahepatic lipid accumulation in obese female patients [6] and amelioration of macrovesicular steatosis in NASH [7], elimination of elevated plasma triglyceride and cholesterol levels in hypercholesterolemia [8], reduced LDL [9] as well as improved insulin sensitivity in insulin-resistant individuals [10], increase in antioxidant capacity [7], broad antibacterial activity [11, 12], and inhibition of inflammation including in cardio- and cerebrovascular patients [9, 13] have all been attributed to whey protein constituent intake (lactoferrin, immunoglobulins, glutamine, lactalbumin, and their peptides) in interventional clinical trials. …”
Section: Introductionmentioning
confidence: 99%